2017
DOI: 10.5604/01.3001.0010.5360
|View full text |Cite
|
Sign up to set email alerts
|

Study of Textile Waste Generation and Treatment in Lithuania

Abstract: The constantly encouraged worldwide production and consumption of textile products is leading to an increase in wastes, which causes environmental problems. This research is aimed at identifying the present state of textile waste generation and treatment in Lithuania and compare the trends obtained with other EU countries. The investigation is based on statistical data of textile waste generation and management from 2009 to 2014 in Lithuania. Municipal textile wastes and those from the leather, fur and textile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…e experimental results showed that all the parameters except TDS for 20% fly ash coagulant dosage were within the permissible limits. Since TDS parameters are a superior-strength influencing factor in the concrete matrix, the coagulant dosages are extended to 25% by the weight of the effluent [27]. From the experimental observations, the optimal coagulant dosages of fly ash are identified as 25% by weight of the effluent (TFA5) listed in Table 3.…”
Section: Comparison Of Chemical Properties Of Potable Water and Treated Effluentmentioning
confidence: 99%
“…e experimental results showed that all the parameters except TDS for 20% fly ash coagulant dosage were within the permissible limits. Since TDS parameters are a superior-strength influencing factor in the concrete matrix, the coagulant dosages are extended to 25% by the weight of the effluent [27]. From the experimental observations, the optimal coagulant dosages of fly ash are identified as 25% by weight of the effluent (TFA5) listed in Table 3.…”
Section: Comparison Of Chemical Properties Of Potable Water and Treated Effluentmentioning
confidence: 99%
“…The issue of sustainable supply chain management in the textile industry is becoming increasingly important. This is due to the fact that enterprises operating in the textile and clothing industry are particularly exposed to the occurrence of social and environmental problems [10] both in the production phase and entire supply chain. As Coster [6] rightly emphasises, environmental issues arise at all stages of the textile and apparel supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…2 Such high consumption of textiles and clothing, among other environmental problems, leads to a huge amount of waste from these products; unfortunately, the prevailing practice for the treatment of textile waste is landfilling. [2][3][4][5][6][7][8] In many European countries, textile waste is disposed of simply by burying it with other household waste or by incineration. According to a report by the Global Fashion Agenda & The Boston Consulting Group, "Pulse of the Fashion Industry.…”
mentioning
confidence: 99%